Bromate and trace metal levels in bread loaves from outlets within Ile-Ife Metropolis, Southwestern Nigeria - J.A.O. Oyekunle; A.S. Adekunle; A.O. Ogunfowokan; G.O. Olutona; O.B. Omolere (Toxicology Reports, 2014)
Bread loaves randomly sampled from nine outlets and bakeries within Ile-Ife were analysed to determine their safety levels for human consumption with respect to bromate and trace metal contents. Bromate determination was carried out via spectrophotometric method while trace metals in the digested bread samples were profiled using Flame Atomic Absorption Spectrophotometer. Bromate levels in the analyzed bread samples ranged from 2.051 ± 0.011 μg/g to 66.224 ± 0.014 μg/g while the trace metal levels were of the order: 0.03–0.10 μg/g Co = 0.03–0.10 μg/g Pb < 0.23–0.46 μg/g Cu < 2.23–6.63 μg/g Zn < 25.83–75.53 μg/g Mn. This study revealed that many bread bakers around Ile-Ife had not fully complied with the bromate-free rule stipulated by NAFDAC contrary to the “bromate free” inscribed on the labels of the bread. The bread samples contained both essential and toxic trace metals to levels that could threaten the health of consumers over prolonged regular consumption.